tert-Butyl 2-(1H-benzimidazol-1-yl)acetate. - N Al-Mohammed, N.; Alias, Y.; Abdullah, Z.; Khaledi, H. (International Union of Crystallography, 2012)
In the title compound, C(13)H(16)N(2)O(2), the planes of the benzimidazole ring system and the acetate O-C=O fragment make a dihedral angle of 84.5 (3)°. In the crystal, mol-ecules are connected through C-H⋯N hydrogen bonds to form infinite chains in the [-110] direction.